Struktur Histologi Trabekula Femur Mencit (Mus musculus L) Orkidektomi Pasca Pemberian Ekstrak tempe Kedelai - Susantin Fajariyah; Siti Nafi’atul Muta’alimah; Eva Tyas Utami; Asmoro Lelono; Husnatun Nihayah (JURNAL BIOS LOGOS, 2024)
Testosterone deficiency is caused by, among other things, old age, chronic disease, and testicular cancer, which results in decreased bone density. Estrogen plays a more important role in the process of bone growth and resorption than the hormone testosterone. Therefore, to prevent a decrease in density in conditions of testosterone deficiency, it is necessary to administer external phytoestrogens, including tempeh, containing isoflavones deidzein dan genistein. The aim of this study was to determine the effect of administering tempeh extract on the histological structure of the femoral trabeculae of orchidectomized mice. Mice were divided into 4 groups, namely negative control (without orchidectomy), positive control (orchidectomy), and 2 orchidectomy treatment groups, followed by administration of tempe extract at a dose of 0.6 g/ml/day (D1) and 1.2 g/ml/day (D2). Tempeh extract was administered by gavage for 15 days after a 30-day healing period for bilateral orchidectomy. One day after the last administration of tempeh extract, the mice were anesthetized and dissected to remove the femur bones to make preparations using the paraffin method and HE staining. The parameters observed were the number of osteoblasts and osteoclasts and the thickness of the femoral trabeculae. Giving soybean tempeh extract at a dose of 0.6 mg/ml/day by gavage for 15 days can cause an increase in the number of osteoblasts and trabecular thickness, as well as reducing the number of osteoclasts in the femur of orchidectomized mice.